UNDERSTANDING ENGLISH PRONUNCIATION OF JAVANESE STUDENTS IN DUTABANGSA UNIVERSITY - Anindhiasti Ayu Kusuma Asri; Pineda Prima Yoga (Universitas Duta Bangsa Surakarta, 2021)
It is obvious that ESL students in Indonesia have differences in their pronunciation. The aim of this paper is to depict the differing qualities of elocution which analyze in phonetics, and why the differing qualities exist, with center on ESL students' major issues in articulating (Q), (d), (f), (3), (tf), (d), that phonemes are articulated by ESL understudies in Solo Central Java. The research method is based on the principle of descriptive qualitative research. This paper is not talking about the term of error examination or contrastive analysis in articulation but it examines the term interlanguage. The result shows that they can pronounce phonemes (Q), (d), (f), (3), (tf), (d) if they do much practice, and also the subjects has difficulties in removing their mother tongue dialect. In this manner, their mistake is not taken as a mistake but as progress when ESL students learn a second language.